If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.5x + 1 = 7 Reorder the terms: 1 + -0.5x = 7 Solving 1 + -0.5x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -0.5x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + -0.5x = 7 + -1 -0.5x = 7 + -1 Combine like terms: 7 + -1 = 6 -0.5x = 6 Divide each side by '-0.5'. x = -12 Simplifying x = -12
| 4(5n-1)+16=12-3(4-2n) | | 12x^1/x² | | 5b+3+6=19 | | 3/2v=16 | | (x+2)(x-2)=(2x+1)(x-2) | | 2x-(4x-9)=6-x | | 2x-35=27 | | 5x+3(4-6x)=11 | | 5/11=u/10 | | 8y-3=-4y+6 | | 2x-35=37 | | 2x^2+13x+8=2 | | f(a-4)=5x+2 | | 4/5k-6 | | 4/5k--6 | | 100=6x+4 | | 3x+-3=-9 | | 7.3=8.5-0.6x | | 15=8x+3-6 | | -6y=1/4 | | (2x-4)*x=100 | | 3x/(x^2-x-20) | | 3x/x^2-x-20 | | 1nx=6 | | 2x-4*x=100 | | C=8pieg | | y=-3z-4 | | 1/(3y)=1/24 | | 3(7+w)=2(6+w) | | -25=4x-4 | | 7.4x-3.8=18.4 | | 6(x+4)+2=8x-2(x-5) |